2004
DOI: 10.55444/2451.7321.2004.v42.n2.3808
|View full text |Cite
|
Sign up to set email alerts
|

O papel dos Fundos de Participação dos Estados - FPE na convergência da renda per capita dos estados brasileiros

Abstract: O trabalho busca verificar a existência de convergência absoluta da renda per cápita dos estados brasileiros existentes no período 1937 a 1999 a través da análise de beta convergência (existência de relação inversa entre PIB inicial e taxa de crescimento) e de convergência (queda da variância entre os PIB's dos estados), adotando a metodologia de estimação de Barro & Sala-i-Martin (1992). Observa-se convergência apenas no período 1969 a 1999. Resultado também encontrado por outros autores. Em seguida, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…The convergence identified in this study was also observed in Nunes and Nunes (2005). The authors discovered a convergence of per capita income from 1969 to 1999.…”
Section: The Reduction Of Regional Inequality In Brazilsupporting
confidence: 76%
See 1 more Smart Citation
“…The convergence identified in this study was also observed in Nunes and Nunes (2005). The authors discovered a convergence of per capita income from 1969 to 1999.…”
Section: The Reduction Of Regional Inequality In Brazilsupporting
confidence: 76%
“…The subject, albeit important, has not been extensively debated in scholarly circles. Nunes and Nunes (2005) used Barro andSala-i-Martin's (1991 e 1992) estimation approach to investigate the existence of both absolute and conditional convergence of per capita income across Brazilian states between 1937 and 1999. They found convergence only from 1969 to 1999, partly attributable to the rise in transfer incomes.…”
Section: Introductionmentioning
confidence: 99%
“…Em um contexto de forte mercantilização, a universalização da saúde é um dos maiores desafios do Governo Federal. Nesse sentido a Carta Magna promulgada em 5 de outubro de 1988 deu um grande passo, e é considerada um marco divisor quando definiu, no seu artigo 9 Foram de grande importância as contribuições de Costa (2002), Lazzari (2003) Públicos e da sociedade, destinadas a assegurar os direitos relativos à saúde, à previdência e à assistência social." (Brasil, 1998).…”
Section: Sistema úNico De Saúde (Sus) E Fundo Estadual De Saúde (Fes)unclassified